Inter-Role Conflicts And Women Sales Workers’ Well-Being: The Moderating Role Of Control, Involvement And Recovery - Mohamed Shah Redza, Sakeena Zahidah (2022)
The purpose of this research is to examine empirically whether inter-role conflicts (work-family conflict and family-work conflict) affect women sales workers’ well-being. Furthermore, to examine how the role of control, involvement and recovery can moderate the relationship between inter-role conflicts and employee well-being.